Penerapan Teknik Assertive Training untuk Meningkatkan Keterbukaan Diri dalam Komunikasi Antar Teman Sebaya - Saputri, Wiwi; Alam, A.Aztri Fitrahyani; Salmiati, Salmiati (ILIN Institute, 2023)
Application of Assertive Training Techniques to Increase Self-Openness in Communication Between Peers of STKIP Students Andi Matappa. Thesis. Guided by Nurhidayatullah and H. Arifin Dia, STKIP Guidance and Counseling Study Program Andi Matappa.The purpose of this study is: (1) To find out the picture of the application of assertive training techniques in increasing self-openness among stkip student peers Andi Matappa. (2) To find out the effectiveness of assertive training techniques to increase self-openness among stkip student peers Andi Matappa.This study uses an experimental.Data collection uses questionnaires and observations. Data analysis uses inferential statistical analysis, i.e. z-test.The results showed that: (1) The application of assertive training techniques to increase self-openness in communication between peers of STKIP students Andi Matappa has a positive influence in increasing self-openness in communication between stkip student peers Andi Matappa, which is seen from the aspects observed at the time of the application of assertive training techniques that have increased at each meeting. Increased activeness at each meeting indicates that students accept the application of assertive training techniques in increasing openness in communication between stkip student peers Andi Matappa. (2) The application of Assertive Training Techniques can Increase Self-Openness in Communication Between STKIP Student Peers Andi Matappa.